Cognitive and behavioral dysfunction in schizophrenia - Moustafa, Ahmed A., 1977- (Academic Press, an imprint of Elsevier, 2021)
According to the World Health Organization, schizophrenia affects more than 21 million people worldwide, causing distortions in thinking, perception, emotions, language, sense of self, behavior, and hallucinations. Cognitive and Behavioral Dysfunction in Schizophrenia provides an overview of topics and theories related to cognitive dysfunction in schizophrenia. This book discusses what schizophrenia is and its relationship with the cognitive domains including, but not limited to, learning, working memory, attention, and both deductive and inductive reasoning. This book also reviews theories as to why some individuals develop schizophrenia following cannabis and amphetamine abuse and how these relate to additional cognitive problems. The book further discusses recent topics related to religious delusions in psychotic patients, impact of sleep on psychosis, how urban life increases the likelihood of developing schizophrenia, as well as sexual dysfunction in schizophrenia patients. Unlike other books, Cognitive and Behavioral Dysfunction in Schizophrenia covers many cognitive domains related to the occurrence and development of positive and negative symptoms of schizophrenia. Advanced students and researchers in cognitive and behavioral neuroscience, psychology, psychiatry, and psychotherapy will find it useful for a well-rounded understanding of the subject. Covers neural and behavioral studies addressing the symptomology of schizophrenia Discusses recent studies of the relationship between cognition and schizophrenia symptoms Reviews the development of schizophrenia due to genetic and environmental factors